DETERMINATION OF CREDIT RISK DIVERSIFICATION - Nabila, Amabel (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to evaluate the factors affecting credit risk or Non Performing Loans by using 10 banks that are the main entities of the Financial Conglomerate from 2015 to 2020 as samples. Sample selection was done by using the purposive sampling method. The variables tested were Non Performing Loan (NPL) as the dependent variable, credit risk diversification based on the type of use (HHI1) and the economic sector (HHI2), and Operational Efficiency Ratio (OER) as the independent variables, and Good Corporate Governance as the moderating variable. The analytical methods employed were descriptive statistics, classical assumption test, panel data regression analysis and model feasibility test. The findings revealed HHI1 and HHI2 are insignificant on credit risk (NPL). However, the OER is positive and significant to the NPL. Then, GCG is unable to moderate the effect of credit risk diversification by HHI1 and OER on NPL. However, GCG is positively and significantly moderate the effect of HHI2 on NPL.Â Keywords : Bank, Diversification, NPL